Menjaga Warisan Budaya: Adaptasi Praktik Konseling Indigenous Terhadap Era Digital di Kota Pekalongan - Zulfa, Nadhifatuz; Maskhur, Maskhur; Subhi, Muhamad Rifa`i Subhi (Jurnal Bimbingan dan Konseling Islam, 2024)
This research aims to investigate how Indigenous counseling practices in the city of Pekalongan adapt to the digital era while preserving local cultural heritage and traditions. The city of Pekalongan has a rich cultural heritage, including counseling practices deeply rooted in the culture and values of the local community. However, with the rapid advancement of digital technology, counseling practitioners are faced with new challenges in maintaining traditional aspects while harnessing the potential of technology. This research uses a qualitative approach to gain in-depth insights into the adaptation strategies employed by indigenous counseling practitioners in the city of Pekalongan. Data were collected through interviews with experienced counseling practitioners, as well as observations of their interactions with clients in a digital context. The research results show that indigenous counseling practitioners in Pekalongan City adopt diverse indigenous approaches and integrate digital technology into their practices without losing cultural roots and traditional values. They developed strategies to maintain the authenticity of Indigenous counseling practices while leveraging technological features to enhance service accessibility and the effectiveness of counseling interventions with local wisdom.